MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI POWTOON PADA PADA MATERI INTI ATOM DAN RADIOAKTIVITAS DALAM UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF SISWA SMA/SEDERAJAT KELAS XII - Melani, Suci Dila; M.Nor, M.Nor; Irianti, Mitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Efforts to improve cognitive learning outcomes and overcome students' difficulties in understanding abstract material on atomic nuclei and radioactivity, research on the development of learning media using the Powtoon application for learning physics in class XII SMA/equivalent is carried out. The purpose of this study was to produce a learning media using the powtoon application on valid atomic nuclei and radioactivity. This study uses the Research and Development method with the ADDIE development model which in its implementation is only carried out until the development stage. The data was obtained from the assessment given by the validator to the media that had been made using the validation assessment sheet. The results showed that the media validity assessment in the media presentation aspect got a score of 3.9 with a very high category , the audio aspect scored 3.75 in the Very High category , the emphasis aspect with a score of 3.3 categories. High, the aspect of balance with a score of 3.67 in the Very High category. In the form aspect, the score is 3.63 in the Very High category and in the color aspect, the score is 3.55 in the Very High category. In the assessment of material validation in the aspect of relevance, the score was 3.3 with the Very High category, the accuracy aspect of the score was 3.62 in the Very High category, and in the content aspect, the score was 3.4 with the High category. and in the language aspect, the score was 3.4 with the High category. Thus the learning media using the application of powtoon on the atomic nucleus and radioactivity in an effort to improve cognitive learning outcomes for class XII high school students can be declared valid and worthy of being tested in physics learning at school.Key Words: Learning Media, Powtoon Applications, Atomic Core and Radioactivity, Cognitive Learning Outcomes.